Optimalisasi Canva dan Akun Belajar.id dalam Pembuatan Bahan Ajar Kreatif Untuk Guru - Ariyanto, Arif Setia Sandi; Mangku Negara, Iis Setiawan; Feriyanto, Yanuar (Universitas Methodist Indonesia, 2024)
A training program on the use of Canva, utilizing Belajar.id accounts, has been conducted to enhance the skills of vocational school teachers in creating creative teaching materials. This article describes the training methods and the benefits teachers gain from leveraging Canva to produce engaging and interactive educational content. The training was designed practically to accommodate the needs of teachers from various disciplines and tailored to the context of vocational education. This activity showed a significant improvement in teachers' ability to use design-based technology to enrich the learning process. The implications of this program can serve as a guide for educational institutions in designing effective training programs, supporting digital transformation in education, and strengthening teachers' competencies in creating innovative and relevant learning experiences for students.